«Fratelli tutti» Challenges Europe - Martínez, Julio L. (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2021)
This article reviews the most acute fronts of conflict facing the European Union, in the light of the social teachings of Pope Francis, especially his last Encyclical Fratelli tutti and the five speeches addressed to the «Old Continent» during these eight years of Pontificate. The reality of Europe today is that it is suffering from the harsh impacts of the pandemic, Jihadist terrorism, and immigration, as well as multiple crises in its institutions, frequently dominated by technocratic logic, and is becoming a fertile ground for Populism, Nationalism and Neoliberal proposals. Pope Bergoglio has addressed, on several occasions, societies in the process of political integration in times of great turbulence, asking them to constantly safeguard community values, the transcendent dignity of the human being, the culture of encounter and multipolarity/transversality in addressing problems. Likewise, he also asks them not to forget the unifying memory of the past, to face the present and to open the way to a future of hope, with responsibility towards the entire world and all peoples.
Keywords: Fratelli tutti; Pope Francis; European Union; crisis; community; populism; peoples